Pitfalls and Limitations of Platelet Counts and Coagulation Tests in the Neonatal Intensive Care Unit - Davenport, Patricia; Sola-Visner, Martha (Current Pediatric Reviews, 2023)
The assessment of hemostasis and the prediction of bleeding risk are of great importance to neonatologists. Premature infants are at an increased risk for bleeding, particularly intra-cranial hemorrhages (most commonly intra-ventricular hemorrhages (IVH)), gastrointestinal hemorrhages, and pulmonary hemorrhages. All severe bleeding, but especially severe IVH, is associated with poor neurodevelopmental outcomes, and other than prenatal steroids, no intervention has reduced the incidence of this serious complication. As a result, there is a need in neonatology to more accurately identify at-risk infants as well as effective interventions to prevent severe bleeding. Unfortunately, the commonly available tests to evaluate the hemostatic system were established using adult physiologic principles and did not consider the neonate's different but developmentally appropriate hemostatic system. This review will describe the changes in the platelet count and tests of hemostasis throughout development, the limitations of these tests to predict neonatal bleeding and the utility of treating abnormal results from these tests with platelet and/or fresh frozen plasma (FFP) transfusions in non-bleeding infants.
Keywords: hemostasis